Isolated Pancreatic Tuberculosis Mimicking Pancreatic Cancer: A Diagnostic Challenge - Bhurwal, Abhishek (Case Rep Gastrointest Med, 2018)
Isolated pancreatic tuberculosis is an exceedingly rare condition, even in areas of the world where the disease is highly prevalent. Abdominal tuberculosis is a common form of extrapulmonary tuberculosis but involvement of the pancreas is very rare. We report a case of isolated pancreatic tuberculosis presenting as a pancreatic mass in a patient with persistent abdominal pain and jaundice. Clinically and radiologically, the mass mimicked a malignant pancreatic tumor with a vastly different prognostic implication and therapeutic approach. Endoscopic ultrasound with fine-needle aspiration (EUS-FNA) can provide valuable diagnostic information in this scenario. After the tissue showed evidence of acid-fast bacilli and the cultures showed growth of Mycobacterium tuberculosis, antituberculosis therapy was initiated. Conservative management is usually successful in alleviating symptoms and leading to a cure. The excellent response to ATT makes it imperative that these patients are diagnosed early and managed appropriately to avoid unnecessary surgery and associated morbidity.